Logoplaste: implementation of flexible packaging technology and internationalization to Nigeria - Miguel, Catarina Cordeiro Rodrigues (2017)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics